KONSEP MANAJEMEN PRODUKSI DAN DESAIN PEMASARAN PADA FILM FIKSI “CAKHRA KALA” - Robi’atul Yamania G; I Komang Arba Wirawan; Desak Putu Yogi Antari Tirta Yasa (CALACCITRA: JURNAL FILM DAN TELEVISI, 2021)
The local film industry was on the brink of collapse in 2010 to 2011. The quality and theme of the film, which only pursued its sales without regard for the value it contained, is one of the reasons why Indonesia has lost interest in local films. Some observers note that the decline occurred as the saturated audience continues to be fed with the film formulaics. As a result, audiences' trust in the quality of Indonesian films was sparked. Furthermore, the perceived deficiencies from local films are the lack of managerial aspects of production regulated by the producer, as well as the resulting marketing plans. In this regard the writer formulates the problem that will be discussed in writing, which is the concept of production management and marketing design in the fictional film "Cakhra Kala". Through the film "Cakhra Kala" the writers tried to take care of the phenomenon. In spite of that "Cakhra Kala" was present with the time frame concept and time overlap in the Indonesian film industry makes it so interesting. The study aims to create a short film by knowing the steps of production management, the standard cultivation prosedure, and the marketing design that a film producer can make. The method of collecting data related to the management of a film and marketing design is literature and observation by reading books on film and watching films of the genre, mysteries, and horror. Research shows that creating good production management measures for the smooth production of films is by using management theories detailed into four elements of planning, organization, direction, and supervision. Then, when viewed from the marketing side, a film aimed at attracting the audience should be promoted to a segment it aims at, based on the use of promotional theory that has been finely defined into five aspects, including market opportunities, aiming for the spectator rate, using the right market timing, having the appeal of the spectators, and maintaining the quality of production. And film would be marketed through festivals and screenings.